Do as I Say and Do as I Do: Teacher Educators’ Narratives about Urban Teaching - Grace McDaniel; Harriett Fayne; Susan Constable; Deanne Knoblauch; Patricia Ryan; Adele Weiss (Networks: An Online Journal for Teacher Research, 2008)
Teacher educators share much in common with their pre-service candidates, but neither group resembles the increasingly diverse PreK-12 student population in cities across the United States. In the words of Gary Howard (1999): How can you teach what you don’t know? A group of faculty members at a small, suburban liberal arts college decided to address this dilemma head-on by creating an urban teaching group. In addition to reading about and discussing important issues related to urban education and culturally responsive pedagogy, we participated in community mapping with early childhood candidates and were assigned to inner-city elementary classrooms. Across a tenweek term, we observed, tutored, and taught lessons under the supervision of cooperating teachers, many of whom were our own graduates. Through direct experience, reflection, and dialogue, we challenged our assumptions and examined the realities of teaching in an urban setting.